Factors affecting auditors’ decisions to adopt Big Data analytics: a mixed method study - Moath Abdelkarim Abu Al Rob; Mohd Nazli Mohd Nor; Zalailah Salleh; Alia Majed Khalaf (Retos: Revista de Ciencias de la Administración y Economía)
The purpose of the present study was to address the primary research question: “To what extent do perceived ease of use (PEOU) and perceived usefulness (PU) explain auditors’ behavioral intentions (BI) to adopt big data analytics (BDA) in auditing firms in Palestine?" A mixed-method approach was utilized, integrating quantitative data from a census survey of 94 auditors at the Big Four accounting firms in Palestine, which achieved an 86% response rate, with qualitative data from semi-structured interviews conducted with 9 auditors at the managerial level or higher. This methodological combination strengthens the validity and reliability of the research outcomes. The findings revealed that PU directly influences auditors' intentions to adopt BDA, and PEOU also affects BI to adopt, but not with the same significance. The study’s findings supported the use of the Technology Acceptance Model (TAM), indicating that auditors are more likely to adopt BDA if they perceive it as useful for their audit firms and if it helps achieve the required efficiency.